4성분계 인산염에서 금속의 부분 치환을 통한 알칼리금속 stoichiometry의 제어 - 김경호 (The Graduate School, Ajou University, 2015)
Due to the ionic mobility of alkali metal ions, alkali metal trivalent metal phosphates, A3 M 2 (PO4)3(M = Fe, Ti, V, Sc) have been widely investigated as materials for rechargeable batteries. It has been reported that the amount of alkali metals can be determined in accordance with the oxidation states of metals(M) and alkali metal occupancies are profoundly related to the ionic conductivities. The structure of these phases are composed of the usual framework built up from corner-sharing MO6 octahedra and PO4 tetrahedra and alkali metal ions in the empty channels of the framework. Partial replacement of M with metals of different oxidation states have lead us to find new mixed-metallic phases with non-stoichiometric metal contents. As a result, new quaternary phosphates, Li2-1.5xTi2-xMx(PO4)3 (M= Nb, Ta) and Na3-2xV2- xNbx(PO4)3 have been prepared with the use of alkali metal halide fluxes and their crystal structures have been investigated by single crystal X-ray diffraction techniques. Compounds in the Li2-1.5xTi2-xMx(PO4)3 (M = Nb, Ta) system are isostructural and they crystallize in the space group Pbcn of the orthorhombic system with a= 12.0927 (4) ~ 12.1594 (3) Å, b= 8.6274 (3) ~ 8.6732 (3) Å, c= 8.6991 (3) ~ 8.7367 (2) Å, V= 907.56 (5) ~ 921.38 (4) Å 3. The frameworks remain intact and the Li ions stay in the channel. The three crystallographically independent Li sites are found in the structure and they are not occupied equally. In this work, relationships between stoichiometry of Li and the sum of the oxidation states of each metal are discussed along with the occupational behavior of Li+ ions over the three Li sites. The classical charge balances of the title compounds can be represented as [Li+]2-1.5x[Ti3.5 +]2-x[M5+]x[P5+]3[O2-]12 (M= Nb, Ta) The single-crystalline mixed metallic phosphates, Na3-2xV2-xNbx(PO4)3, also have been prepared with the use of the metal halide, NaCl as a reactive flux. This compounds have been structurally characterized by single-crystal X-ray diffraction techniques. The title compound crystallize in the space group R-3c of the trigonal system.(a= 8.6045 (3) ~ 8.6576 (8) Å, c= 22.041 (5) ~ 22.1121 (9) Å, V= 1417.80 (13) ~ 1431.2 (4) Å 3). The framework of Na3-2xV2- xNbx(PO4)3 is built via corner-sharing MO6 octahedra and PO4 tetrahedra. There are two crystallographically independent Na sites in the structure and these sites are occupied by Na+ ions for charge neutrality. The occupancy of the Na1 site seems to be preferred over that of the Na2 site due to the stronger ionic interactions through stronger Na-O interactions. The classical charge valences of the title compounds can be represented by [Na+]3-2x[V3+]2- x[Nb5+]x[P5+]3[O2-]12.
학위논문(석사)--아주대학교 일반대학원 :에너지시스템학과,2015. 2
Keywords: stoichiometry; 알칼리금속